HIV-1 Structural Proteins Serve as PAMPs for TLR2 Heterodimers Significantly Increasing Infection and Innate Immune Activation - Henrick, Bethany M.; Yao, Xiao-Dan; Rosenthal, Kenneth Lee; , the INFANT study team (Frontiers in Immunology, 2015)
Immune activation is critical to HIV infection and pathogenesis; however, our understanding of HIV innate immune activation remains incomplete. Recently we demonstrated that soluble TLR2 (sTLR2) physically inhibited HIV-induced NFκB activation and inflammation, as well as HIV-1 infection. In light of these findings, we hypothesized that HIV-1 structural proteins may serve as pathogen-associated molecular patterns (PAMPs) for cellular TLR2 heterodimers. These studies made use of primary human T cells and TZMbl cells stably transformed to express TLR2 (TZMbl-2). Our results demonstrated that cells expressing TLR2 showed significantly increased proviral DNA compared to cells lacking TLR2, and mechanistically this may be due to a TLR2-mediated increased CCR5 expression. Importantly, we show that HIV-1 structural proteins, p17, p24, and gp41, act as viral PAMPs signaling through TLR2 and its heterodimers leading to significantly increased immune activation via the NFκB signaling pathway. Using co-immunoprecipitation and a dot blot method, we demonstrated direct protein interactions between these viral PAMPs and TLR2, while only p17 and gp41 bound to TLR1. Specifically, TLR2/1 heterodimer recognized p17 and gp41, while p24 lead to immune activation through TLR2/6. These results were confirmed using TLR2/1 siRNA knock down assays which ablated p17 and gp41-induced cellular activation and through studies of HEK293 cells expressing selected TLRs. Interestingly, our results show in the absence of TLR6, p24 bound to TLR2 and blocked p17 and gp41-induced activation, thus providing a novel mechanism by which HIV-1 can manipulate innate sensing. Taken together, our results identified, for the first time, novel HIV-1 PAMPs that play a role in TLR2-mediated cellular activation and increased proviral DNA. These findings have important implications for our fundamental understanding of HIV-1 immune activation and pathogenesis, as well as HIV-1 vaccine development.